2011
DOI: 10.1097/eja.0b013e3283430802
|View full text |Cite
|
Sign up to set email alerts
|

Antishivering effects of two different doses of intrathecal meperidine in caesarean section: a prospective randomised blinded study

Abstract: The use of intrathecal meperidine for caesarean section during spinal anaesthesia for the prevention of shivering cannot be recommended as its use is associated with increased incidence of nausea and vomiting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 17 publications
2
41
0
2
Order By: Relevance
“…However, owing to increasing incidence of nausea/vomiting they concluded that they do not agree with intrathecal meperdine. Results of the current study is in agreement with Khan et al (9) in terms of shivering, however, the incidence of nausea/vomiting was not higher in the 2 studies groups in comparison to the control group in our study. The reason of this discrepancy between 2 studies is related to the dose of meperdine, we used 10 mg intrathecal meperidine, which is less than the dose used in the above study, which could be the reason for a lower adverse effect of intrathecal meperdine.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…However, owing to increasing incidence of nausea/vomiting they concluded that they do not agree with intrathecal meperdine. Results of the current study is in agreement with Khan et al (9) in terms of shivering, however, the incidence of nausea/vomiting was not higher in the 2 studies groups in comparison to the control group in our study. The reason of this discrepancy between 2 studies is related to the dose of meperdine, we used 10 mg intrathecal meperidine, which is less than the dose used in the above study, which could be the reason for a lower adverse effect of intrathecal meperdine.…”
Section: Discussionsupporting
confidence: 83%
“…Results of current study showed that intrathecal meperidine as well as morphine did not increase the side effects in comparison with the control group. Khan et al (9) found an association between the increased incidence of nausea and vomiting by adding meperidine to subarachnoid administered bupivacaine, and also by higher doses of intrathecal meperidine (25 mg) in comparison to a lesser dose (12.5 mg). Bhukal et al (13) showed that the incidence of shivering was lower in the meperidine 0.5 mg/kg than 0.3 mg/kg but none of these doses of meperidine had a statistically significant adverse effect on patients, compared with placebo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies have documented the antishivering effects of IM but have not dilated on the adverse effects of nausea and vomiting either because they were not their primary end points or else their sample size was too small to reveal these side effects. Others have mostly dwelt on the adverse effects of IM which had been obviously annoying for the patients and thus it could be concluded that either the use of IM be altogether avoided if possible or else its dose be curtailed to the minimum possible level to obviate the agonizing side effects of nausea, vomiting and pruritus [7][8][9]. …”
mentioning
confidence: 99%
“…El temblor en el período intraoperatorio se inhibe durante la anestesia general; y por lo tanto los pacientes son más propensos a la hipotermia y a los temblores en el período postoperatorio. Por ende, existen 2 elementos importantes para el temblor inducido por la anestesia regional: 1) el efecto deseado de temblores, o sea, la preservación de calor por el aumento de la tasa metabólica basal, y 2) los efectos no deseados del temblor (aumento de O 2 venoso, desaturación, extracción de O 2 del miocardio, incomodidad y ansiedad por parte de la paciente y, posiblemente, para el manejo del cirujano y la monitorización de los artefactos para el anestesiólogo (por ejemplo, pO 2 sistólica, presión arterial no invasiva y artefactos de ECG en los temblores del período intraoperatorio) 4,5 . Por tanto, los autores deben medir la temperatura corporal materna para evaluar así los efectos deseados.…”
Section: Importance Of Maternal Body Temperature Recording After Injeunclassified